RuvBL1 Maintains Resistance to TRAIL-Induced Apoptosis by Suppressing c-Jun/AP-1 Activity in Non-Small Cell Lung Cancer - Li, Hao; Zhou, Taoran; Zhang, Yue; Jiang, Hengyi; Zhang, Jing; Hua, Zichun (Frontiers in Oncology, 2021)
Lung cancer remains the leading cause of cancer-related deaths in the world. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) as a potential anticancer agent induces selective apoptotic death of human cancer cells. Unfortunately, approximately half of lung cancer cell lines are intrinsically resistant to TRAIL-induced cell death. In this study, we identified RuvBL1 as a repressor of c-Jun/AP-1 activity, contributing to TRAIL resistance in lung cancer cells. Knocking down RuvBL1 effectively sensitized resistant cells to TRAIL, and overexpression of RuvBL1 inhibited TRAIL-induced apoptosis. Moreover, there was a negative correlation expression between RuvBL1 and c-Jun in lung adenocarcinoma by Oncomine analyses. High expression of RuvBL1 inversely with low c-Jun in lung cancer was associated with a poor overall prognosis. Taken together, our studies broaden the molecular mechanisms of TRAIL resistance and suggest the application of silencing RuvBL1 synergized with TRAIL to be a novel therapeutic strategy in lung cancer treatment.